PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS KURIKULUM MERDEKA UNTUK MENINGKATKAN KOMPETENSI GURU MGMP BAHASA ARAB DI BOJONEGORO : PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS KURIKULUM MERDEKA UNTUK MENINGKATKAN KOMPETENSI GURU MGMP BAHASA ARAB DI BOJONEGORO - Mufid, Miftahul; Diantika, Devi Eka; Kholid, Ahmad Amirul (Al-Umron : Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service Program (PkM) titled “Assistance in Developing Interactive Learning Media Based on the Merdeka Curriculum to Improve the Competence of MGMP Arabic Language Teachers in Bojonegoro” has achieved various significant outcomes. Through training, workshops, and collaboration between MGMP Arabic Language teachers, schools, and the Bojonegoro Education Office, this program has successfully enhanced teachers’ competence in integrating technology into teaching. Innovative and suitable interactive learning media designs for Arabic language learning have been produced. The implementation of this media in several schools in Bojonegoro has proven beneficial in increasing students’ interest and motivation in learning. Additionally, the established collaboration has created synergy in supporting the development of teacher competence and the implementation of the service program. Dissemination of results through seminars, workshops, and scientific publications has had a broader impact on raising awareness about the importance of utilizing technology in education. The sustainability plan of the program also commits to continuously developing and expanding the use of interactive learning media in all schools in Bojonegoro. With positive and sustainable achievements, this program has made a tangible contribution to improving teacher competence, the quality of learning, and students’ interest in the Arabic language. This program is an important initial step in advancing the education system in Bojonegoro, creating a more innovative, dynamic, and relevant learning environment in the digital era.